2.1) ( 4x^2 +6x + 6) / (3-4x)^2
2.2)-2xsin(x^2)
Пошаговое объяснение:
2.1) есть формула (x/y)' = ( x'y - xy' ) / y^2
( (x^2+2x)' * (3-4x) - (x^2+2x) * (3-4x)' ) / (3-4x)^2
( (2x+2)(3-4x) - (x^2+2x)(-4) ) / (3-4x)^2
( 4x^2 +6x + 6) / (3-4x)^2
2.2) (cos(a) )'= -sina
(x^2 )' = 2x
-sin(x^2) * 2x
-2xsin(x^2)
2.1) ( 4x^2 +6x + 6) / (3-4x)^2
2.2)-2xsin(x^2)
Пошаговое объяснение:
2.1) есть формула (x/y)' = ( x'y - xy' ) / y^2
( (x^2+2x)' * (3-4x) - (x^2+2x) * (3-4x)' ) / (3-4x)^2
( (2x+2)(3-4x) - (x^2+2x)(-4) ) / (3-4x)^2
( 4x^2 +6x + 6) / (3-4x)^2
2.2) (cos(a) )'= -sina
(x^2 )' = 2x
-sin(x^2) * 2x
-2xsin(x^2)